Evaluation of antimicrobial activity of andrographis paniculata extract against staphylococcus aureus / Zayan Nabilah Rasyidah Abd. Razak - Abd. Razak, Zayan Nabilah Rasyidah (2015)
A.paniculata leaves are known to have antimicrobial activities and it is widely used as traditional medicine worldwide. This study investigated the antimicrobial activities of methanolic extract of Saureus (ATCC 25923) by determining the Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC), time-kill assay and the effects of A.paniculata extract on Saureus in SDSPAGE analysis. Several concentration of the A.paniculata extracts were used to determine MIC value and the lowest concentration that can inhibit growth of Saureus was further tested to obtain MBC value. Time-kill assay was performed in 24 hours to determine the incubation period needed for A.paniculata extract to completely kill Saureus. The treated samples (A.paniculata extract and Saureus) and untreated samples (Saureus only) were compared in terms of appearance of cytoplasmic protein bands to determine the effect of treatment. A.paniculata extract showed high antimicrobial activity against Saureus with MIC and MBC value was O.06mglml. The MIC value was able to completely killed Saureus in 24 hours incubation time. Lipase (76 kDa) was identified on SDS-PAGE analysis which was inhibited when treated with A.paniculata extract. The observation suggests that a possible mechanism by which methanolic extract of A.paniculata inhibits Saureus by lowering production of an important protein, lipase. Future work which involves proteomics study on the effects of A.paniculata against Saureus should be pursued.